Institutional aspects of budget relations development in the conditions of territorial development levels differentiation - A. R. Kumpilova; S. K. Khamirzova (Новые технологии)
The article analyzes current issues of fiscal capacity of regions with their own revenues at present stage of economic development of the Russian Federation. It is noted that the balance of the budget is a basic condition that allows regional authorities to fulfill their expenditure commitments. Besides, the article examines the problems of subsidies to regional budgets, identifies the reasons for their occurrence.